The views of practitioners on Malaysian partnering policies for PPP/PFI projects - Abdul Nifa, Faizatul Akmar; Radzuan, Kamaruddin; Mohd Nawi, Mohd Nasrun; Abdul Rahim, Syukran; Ahmed, Vian (2016)
The challenges currently faced by the Malaysian construction industry could be attributed to the industry being multifaceted in nature and comprised of firms forming ‘temporary organizations’ whereby failure in aligning objectives within the team may cause friction, and further creating challenges to project implementation.In response to these challenges, CIDB has identified and recommended partnering as a method to overcome the current problems within the industry.It is crucial that the policies in place should facilitate the practitioners so that the full potential of partnering to overcome the many problems in the Malaysian construction industry can be fully utilized.This paper describes the findings of an exploratory qualitative research to identify if the current policies in place are serving as an enabler for effective partnering or a deterrent to the adoption of partnering by the practitioners in the Malaysian construction industry.It is determined that apart from issues identified from literature review, other factors such as political and legal system influence towards partnering should be considered in formulating effective policies for partnering in the Malaysian construction industry.